Proximate composition, provitamin A retention, and shelf life of extruded orange-fleshed sweet potato and bambara groundnut-based snacks - Honi, Buzo; Muzira Mukisa, Ivan; Mongi, Richard John (Journal of Food Processing and Preservation, 2018)
Evaluating the effect of processing on nutrient content and shelf life is important when developing new products. Six formulations of orange-fleshed sweet potato (OFSP) and bambara groundnut were extruded at a feed rate of 10.15 kg/hr, screw speed of 30 rpm and at 100 and 130 8C in first and second zones respectively. Proximate composition was determined using standard methods. Provitamin A was determined using high-performance liquid chromatography. An untrained panel (n573) was used to determine consumer acceptability. Shelf life was predicted by using peroxide values. Concentration of OFSP or bambara groundnut significantly (p < .05) affected proximate composition of the snacks. Moisture (4.79–8.34 g/100 g), carbohydrates (55.53–78.99 g/100 g) and provitamin (0.54–17.33 mg/100 g) contents increased with increase in proportion of OFSP. Protein (4.08–15.03 g/100 g), fat (4.20–12.74 g/100 g), fiber (5.29–6.46 g/100 g), ash (0.09– 4.80 g/100 g), and energy (366.13–396.9 kcal/100 g) increased with increasing proportion of bambara groundnut in the formulation. Extrusion significantly (p < .05) reduced provitamin A content from 0.90–20.73 to 0.54–17.33 mg/100 g. Presence of OFSP improved provitamin A retention and consumer acceptability. Predicted shelf life (ranged from 118 to 150 days at room temperature) was inversely proportional to the concentration of bambara groundnut.
Keywords: Proximate composition; Orange-fleshed sweet potato; Bambara groundnuts